Pro-health awareness of women in the context of knowledge about risk factors for cervical carcinoma - Lipińska, Anna M.; Karnia, Agnieszka; Macek, Paweł; Ridan, Tomasz; Lipińska-Stańczak, Magdalena (Medical Studies/Studia Medyczne, 2016)
Introduction: The problem of cancer is becoming epidemic in the world. Despite many campaigns that promote prophylaxis, the number of women dying of cervical carcinoma is still high. Broadly defined health education aimed at detecting the disease at an early stage should be an important point of the cervical carcinoma prophylaxis program. Aim of the research : To determine the level of awareness of women surveyed in the context of the risk factors and an analysis of health behaviours. Material and methods: The study was conducted among 108 randomly selected women living in Świętokrzyskie province. The women were between the ages of 20 and 60 years. Results : The study showed that the respondents were able to read properly the causes of the risk of cervical carcinoma, but only about 30% went to a gynaecologist for prophylactic measures. Thirty percent of the respondents had cytology regularly done. Only 8% of the women in the studied group accepted an invitation to screening examinations. The majority of the surveyed women knew the risk factors for cervical carcinoma but they did not translate their knowledge into health behaviours. Most of the respondents did not have regular cytological examinations done. The majority of the surveyed women did not have screening examinations done. Conclusions : Therefore, it is necessary to multiply efforts within the actions preventing cervical carcinoma, and promote a healthy lifestyle and pro-health education.